HUBUNGAN ANTARA KECEMASAN DENGAN HASIL BELAJAR MATEMATIKA SISWA KELAS V SEKOLAH DASAR NEGERI 164 PEKANBARU - Aulia Nurrahmi; Gustimal Witri; Syahrilfuddin Syahrilfuddin (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2019)
Mathematics is one of the subjects that some students fear. Negative things arise when dealing with math in the form of fear. Mathematical anxiety is one of the factors that can disrupt the learning process, so that it can affect students' math learning outcomes. In connection with these problems, the authors carried out a study of class V students of the state primary school 164 Pekanbaru with the aim of knowing the relationship between fear and math learning outcomes. The type of research used is quantitative with the correlational research method. The total population of the study was 148 students and the study sample was 60 respondents. Data collection was carried out in the form of questionnaires and documentation of the learning outcomes of class V. Based on the processed data, a correlation coefficient of -|0.297| was obtained with a tcount of 2.47, which demonstrated a significant relationship between anxiety and mathematics learning outcomes of students from the fifth grade of the Pekanbaru Pekanbaru Elementary School. has the power of weak relationships and negative nature of the relationship. This study concludes that there is a connection between anxiety and the results of learning mathematics in students of class V of the Pekanbaru Elementary School 164.